2011
DOI: 10.1210/jc.2010-1082
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of Thyroid Nodules according to a Management Guideline Based on the BRAFV600E Mutation Status

Abstract: We found that performing BRAF(V600E) mutation analysis on the fine-needle aspiration biopsy specimens was of great help to make a therapeutic decision for thyroid nodules when the fine-needle aspiration biopsy results were equivocal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
125
5
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 20 publications
17
125
5
2
Order By: Relevance
“…5,6,8,9,[12][13][14] The data from these series are summarized in Table 1. It is interesting to note that the overall rate of AUS was 9.7% with only 2 of 8 series reporting AUS rates below the previously recommended threshold of 7%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6,8,9,[12][13][14] The data from these series are summarized in Table 1. It is interesting to note that the overall rate of AUS was 9.7% with only 2 of 8 series reporting AUS rates below the previously recommended threshold of 7%.…”
Section: Resultsmentioning
confidence: 99%
“…We identified PubMed-indexed, peer-reviewed published laboratory experiences using TBS in which the categorical breakdown of all 6 reporting tiers was identified 5,6,8,9,[12][13][14] and supplemented those data with previously unpublished figures from the Massachusetts General Hospital compiled by one of the authors (W.C.F.) from 2006 to 2008 using TBS (a subset of these cases was included in a prior study 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported that the BRAF mutation is a highly accurate marker of malignancy for thyroid nodules sampled by FNAB [205][206][207][208][209]. However, the most frequent diagnostic problems in FNAB samples are indeterminate follicular tumors and suspicion of malignancy according to the Bethesda system.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%